Sodium Fluorescein for Spinal Intradural Tumors - Olguner, Semih Kivanc; Arslan, Ali; Açık, Vedat; İstemen, İsmail; Can, Mehmet; Gezercan, Yurdal; Ökten, Ali İhsan (Frontiers in Oncology, 2021)
Technological innovations in spinal intradural tumor surgery simplify treatment. Surgical treatment of cranial benign and malignant pathologies under a microscope with sodium (Na)-fluorescein guidance has often been reported, but few studies have focused on spinal intradural tumors. We aimed to investigate the usefulness of Na-fluorescein under yellow filter in intradural spinal tumor surgery by retrospectively reviewing cases involving intramedullary and extramedullary tumors operated under the guidance of Na-fluorescein. Forty-nine adult patients with a diagnosis of spinal intradural tumor operated under a yellow filter (560 nm) microscope using Na-fluorescein dye were included in the study. Demographic data, such as age and sex, neurological status, the extent of tumor resection, histopathological diagnosis, Na-fluorescein staining pattern, and its usefulness during surgery were noted and statistically analyzed. Of all recruited patients, 26 women (53.1%) and 23 men (46.9%), were included for analysis. The age range of the patients was 18-64 years, with a mean age of 41.6 ± 13.9. An intradural intramedullary mass was found in 30.6% (n = 15) of the patients, and an intradural extramedullary mass in 69.4% (n: 34). While Na-fluorescein staining was homogeneous in all intradural extramedullary tumors, 73.3% (n: 11) of intradural intramedullary tumors were homogeneous, and 13.3% (n: 2) moderately heterogeneous. In the whole study group, the Na-fluorescein staining pattern was helpful in surgical resection in 47 cases (95.9%). While 34/34 (100%) found it helpful for extramedullary tumors, 13/15 (86.7%) did in intramedullary tumors, and for 2/15 (13.3%) it was not. In conclusion, Na-fluorescein helps in distinguishing tumor from healthy tissue in intradural extramedullary and intramedullary tumor surgery under a yellow filter microscope in most cases, thus providing convenient assistance to surgeons.